Features of self-relation in cosmetological patients with high self-esteem - Yudin, M. (Journal of Education, Health and Sport, 2016)
The aim of the research - to investigate features of self-esteem in patients with cosmetic problems. Contingent and methods. The study conducted at the Medical Center "CA Clinic" during 2014 – 2016 years, 178 women with cosmetic problems participated in the research. Results. Profile in women with high self-esteem characterized by self-confidence, a sense of perfection, perceptions of high own charm and personal qualities, making himself uncritical their shortcomings, self-trust, self-respect, hard confrontation in response to attacks or doubts about their identity from the other people. Overall,self-esteem was disharmonious, high positive self-assessment of own qualities combined with low self-reflection. Conclusions. Cosmetological patients who have high self-esteem constitute a separate category of clients and require the use of psychological measures aimed at harmonizing disharmonious self-relation.